IMF Staff Papers : Volume 1, No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1951)
This paper discusses that the governments of forty-nine countries have accepted the Articles of Agreement of the IMF. They have accepted the Agreement on their own behalf and in respect of all their colonies, overseas territories, all territories under their protection, suzerainty, or authority and all territories in respect of which they exercise a mandate. Although the concept of a fixed par value and of rates of exchange based on it is of fundamental importance under the Articles of Agreement, provision is also made for the retention, adaptation and introduction of multiple currency practices in certain circumstances. Courts are frequently called upon to decide at what rate of exchange one currency shall be translated into another. The courts of many countries have been faced, both before and after the coming into force of the IMF Agreement, with the problem whether they should recognize the effect of the exchange control regulations of other countries.